Study protocol: baby-OSCAR trial: Outcome after Selective early treatment for Closure of patent ductus ARteriosus in preterm babies, a multicentre, masked, randomised placebo-controlled parallel group trial - Gupta, S; Juszczak, E; Hardy, P; Subhedar, N; Wyllie, J; Kelsall, W; Sinha, S; Johnson, S; Roberts, T; Hutchison, E; Pepperell, J; Linsell, L; et al. (BMC, 2021)
BACKGROUND: The question of whether to treat patent ductus arteriosus (PDA) early or wait until symptoms appear remains high on the research agenda for neonatal medicine. Around 7000 extremely preterm babies under 29 weeks' gestation are born in the UK every year. In 40% of cases the PDA will fail to close spontaneously, even by 4 months of age. Untreated PDA can be associated with several serious and life-threatening short and long-term complications. Reliable data to support clinical decisions about PDA treatment are needed to prevent serious complications in high risk babies, while minimising undue exposure of infants. With the availability of routine bedside echocardiography, babies with a large PDA can be diagnosed before they become symptomatic.